IMPLEMENTATION OF THE ACCOUNTING INFORMATION SYSTEM IN THE FINANCIAL MANAGEMENT OF COMMUNITY HEALTH CENTER - Fathul Bahri; Lili Susanti; Nur Azlina; Azwir Nasir; Atami, Aulia Pinto (Riau International Conference on Economics, Business and Accounting, 2024)
This research aims to determine the effect of transparency and accountability on the implementation of the Accounting Information System in the Financial Management of BLUD Community Health Centers. The type of research used in this research is associative research. The data collection technique in this research uses a questionnaire. The sample collection technique used was the nonprobability sampling method. The types of data in this research are primary and secondary data with a total of 152 respondents consisting of heads of community health centers, heads of administration, revenue treasurers and expenditure treasurers at community health centers in Meranti, Bengkalis and Dumai cities, Indonesia. The analytical test tool used is SmartPLS 4. The results of this research show that transparency and accountability have a positive and significant effect on financial management, while the accounting information system has a positive but not significant effect on financial management.